A Survey on Plant Health Monitoring using IoT - et. al., Dr.S.Balaji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Plants are one of the important kind of organisms available over the world. There are so many ways in which plants help the environment and human’s life on the earth by providing food for humans and wildlife. So it is necessary to keep the plants in a healthy manner. Healthy plants leads to a country’s profitable agricultural production. Internet of Things (IOT) has played a vital role in monitoring plants health. It helps farmers by monitoring the plant as well as leads to a greater production. The proposed system is based upon sensors for monitoring. The factors such as soil moisture, pH, temperature, air quality can be determined by using specific sensors with the help of a microcontroller. The values are collected from the sensors. By comparing the already stored value with the collected value we can determine the result. The paper represents the system and considered the detailed information related to the processing of the results.